2020
DOI: 10.1302/2046-3758.12.bjo-2019-0004.r1
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted total knee arthroplasty demonstrates decreased postoperative pain and opioid usage compared to conventional total knee arthroplasty

Abstract: Aims Robotic-assisted total knee arthroplasty (RA-TKA) has been introduced to provide accurate bone cuts and help achieve the target knee alignment, along with symmetric gap balancing. The purpose of this study was to determine if any early clinical benefits could be realized following TKA using robotic-assisted technology. Methods In all, 140 consecutive patients undergoing RA-TKA and 127 consecutive patients undergoing conventional TKA with minimum six-week follow-up were reviewed. Differences in visual anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…Bhimani et al compared 140 consecutive ra-TKAs with 127 conventional TKAs with a minimum follow-up of 6 weeks and found that ra-TKA patients needed lower morphine equivalents versus conventional group by 3.2 mg per day. 16 They also found significantly lower visual analogue scale (VAS) pain scores at 6 weeks associated with lower opioid consumption. 16…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Bhimani et al compared 140 consecutive ra-TKAs with 127 conventional TKAs with a minimum follow-up of 6 weeks and found that ra-TKA patients needed lower morphine equivalents versus conventional group by 3.2 mg per day. 16 They also found significantly lower visual analogue scale (VAS) pain scores at 6 weeks associated with lower opioid consumption. 16…”
Section: Discussionmentioning
confidence: 94%
“…16 They also found significantly lower visual analogue scale (VAS) pain scores at 6 weeks associated with lower opioid consumption. 16…”
Section: Discussionmentioning
confidence: 94%
“…Our findings are consistent with similar patterns of pain improvement with raTKA technique noted in other studies. 14 22 We conclude that raTKA demonstrated improved value compared with mTKA based on lower 90-day EOC cost and improved quality.…”
Section: Discussionmentioning
confidence: 81%
“…Kayani et al [12] compared early postoperative functional outcomes between conventional jig-basedTKAand Mako RA-TKA and found that the RA-TKA group showed reduced pain and decreased analgesic requirements at POD 3. Bhimani et al [21] retrospectively reviewed 140patients undergoing Mako RA-TKAand found that RA-TKA resulted in lower pain levels at both rest and movement at 2 and 6 weeks postoperatively andrequiredless opioid medication. In this study, we reviewed postoperative pain for 14 days in NavioRA-TKA but did not nd signi cant differences in postoperative pain at rest or during movement.…”
Section: Discussionmentioning
confidence: 99%